WHY THE DOTS ARE BLACK ONLY IN THE LATE PHASE OF THE INDOCYANINE GREEN ANGIOGRAPHY IN MULTIPLE EVANESCENT WHITE DOT SYNDROME. (2017) - Gaudric, Alain; Mrejen, Sarah
Abstract : Purpose: To determine what retinal layer is primarily involved in multiple evanescent white dot syndrome compared with acute posterior multifocal placoid pigment epitheliopathy using multimodal imaging including indocyanine green angiography. Methods: Color fundus photographs and fluorescein angiography, ICGA and spectral domain optical coherence tomography images of two typical acute cases, one of acute posterior multifocal placoid pigment epitheliopathy and one of multiple evanescent white dot syndrome, were assessed and compared. Results: In both diseases, white plaques or dots were seen at the posterior pole. The hypofluorescence of acute posterior multifocal placoid pigment epitheliopathy in the early phase of the fluorescein angiography and throughout the ICGA sequence suggested a multifocal choroidal hypoperfusion as the cause of the opacification of the outer retina corresponding to its hyper-reflectivity on spectral domain optical coherence tomography. In multiple evanescent white dot syndrome, there was no choroidal filling defect and the white spots were silent in the early phase of the ICGA, whereas they became black only in the late phase. The outer retina was also altered at the spots. Conclusion: In multiple evanescent white dot syndrome, the late hypofluorescence of the white spots on ICGA was likely due to the absence of ICG uptake by a damaged retinal pigment epithelium. Multiple evanescent white dot syndrome seems as a primary reversible nondestructive retinal pigment epitheliopathy, whereas acute posterior multifocal placoid pigment epitheliopathy is a true choroidopathy. Abstract : In multiple evanescent white dot syndrome, the late hypofluorescence of the white dots on indocyanine green angiography is likely due to the absence of indocyanine green uptake by a damaged retinal pigment epithelium. Multiple evanescent white dot syndrome appears as a primary reversible nondestructive retinal pigment epitheliopathy, whereas acute posterior multifocal placoid pigment epitheliopathy is a true choroidopathy.